Escalation of Commitment and Bankruptcy: The Case of Katerra Industries - Brown, Richard S. (Journal of Management Policy and Practice, 2025)
Escalation of commitment has been defined as disregarding exit as a valid option thereby following a losing course of action even when the negative consequences are known. This paper incorporates escalation of commitment theory in the context of the failure of Katerra Industries. Katerra, backed with 3 Billion of venture capital, attempted to create a vertically integrated modular construction company based on its technological advantages. Instead, the firm expanded at a rate that made the complexity of its operations too difficult to manage properly leading to its Chapter 11 bankruptcy filing in June 2021. This paper employs qualitative empirical research, specifically through a case study utilizing U.S. federal court filings and testimony as the primary data source. The findings support previous escalation of commitment research, generally, and its theoretical underpinnings, namely (i) Subjective Expected Utility Theory and (ii) Self-Presentation Theory.